Epithelioid trophoblastic tumor presenting as a Caesarean scar defect: A case report - Kristin A. Black; Kristen Simone; Cassandra Hirt-Walsh; Jeanelle Sabourin (Elsevier, 2021)
Background: Epithelioid trophoblastic tumor is a rare form of gestational trophoblastic neoplasia. We present the first known case of this rare malignancy presenting as a Caesarean scar defect. Case: A patient with 3 prior Caesarean sections presented with vaginal bleeding 2 months following management of retained products of conception. Her hCG was negative. She underwent surgical repair of a Caesarean scar defect, and pathology was consistent with epithelioid trophoblastic tumor. Conclusion: This case highlights the possibility of malignancy presenting to the general gynecologist as a Caesarean scar defect. The diagnosis of gestational trophoblastic neoplasia should always be considered in the differential diagnosis of a patient with postpartum vaginal bleeding. Limited evidence on fertility conserving treatment of epithelioid trophoblastic tumors does not seem favorable.